Microalgae for high-value products: A way towards green nutraceutical and pharmaceutical compounds - Mehariya, Sanjeet; Goswami, Rahul Kumar; Karthikeysan, Obulisamy Parthiba; Verma, Pradeep (Chemosphere (Oxford), 2021)
Microalgae is a renewable bioresource with the potential to replace the conventional fossil-based industrial production of organic chemicals and pharmaceuticals. Moreover, the microalgal biomass contains carotenoids, vitamins, and other biomolecules that are widely used as food supplements. However, the microalgal biomass production, their composition variations, energy-intensive harvesting methods, optimized bio-refinery routes, and lack of techno-economic analysis are the major bottleneck for the life-sized commercialization of this nascent bio-industry. This review discusses the microalgae-derived key bioactive compounds and their applications in different sectors for human health. Furthermore, this review proposes advanced strategies to enhance the productivity of bioactive compounds and highlight the key challenges associated with a safety issue for use of microalgae biomass. It also provides a detailed global scenario and market demand of microalgal bioproducts. In conclusion, this review will provide the concept of microalgal biorefinery to produce bioactive compounds at industrial scale platform for their application in the nutraceutical and pharmaceutical sector considering their current and future market trends. [Display omitted] •Microalgae are bio-factory that produces high value-added compounds (HVAC) from CO2.•Bioprospecting of microalgae strain enhances biomass yield and HVAC contents.•Genetic engineering boosts the accumulation of HVAC in microalgae.•Microalgae HVAC have nutraceuticals, cosmeceutical and pharmaceutical applications.•High demands for algal HVAC help to develop and sustain the circular bioeconomy.